Detection of gaps between high-intensity focused ultrasound (HIFU)-induced lesions using transient axial shear strain elastograms - Liu, Chenhui (2020)
Purpose: High‐intensity focused ultrasound (HIFU) is becoming an effective and noninvasive treatment modality for cancer and solid tumors. In order to avoid the cancer relapse and guarantee the success of ablation, there should be no gaps left among all HIFU‐generated lesions. However, there are few imaging approaches available for detecting the HIFU lesion gaps in real time during ablation. Methods: Transient axial shear strain elastograms (ASSEs) were proposed and evaluated both numerically and experimentally to detect the lesion gaps immediately after the cessation of therapeutic HIFU exposure. Acoustic intensity and subsequent acoustic radiation force were first calculated by solving the nonlinear Khokhlov–Zabolotskaya–Kuznetzov (KZK) equation. Motion of being‐ and already‐treated lesions during and after HIFU exposure was simulated using the transient dynamic analysis module of finite element method (FEM). The corresponding B‐mode sonography of tissue‐mimicking phantom with two HIFU lesions inside was simulated by FIELD II, and then axial strain elastograms (ASEs) under static compression and transient ASSEs were reconstructed. An ultrasound imaging probe was integrated with the HIFU transducer and used to obtain radio frequency (RF) echo signals at high frame rate using plane wave imaging (PWI). The resulting strains were mapped using the correlation‐based method and block search strategy. Results: Acoustic radiation force from the therapeutic HIFU burst is sufficiently strong to produce significant displacement. As a result, large and highly localized axial shear strain appears in the gap zone between two HIFU‐generated lesions and then disappears after sufficient HIFU ablation (no gap between them). Such capability of detecting the lesion gap is validated at the varied acoustic radiation force density, gap width, and the size of the lesion. In contrast, conventional ASEs using the static compression cannot distinguish whether a gap exists between lesions. Static ASEs and transient ASSEs reconstructed using both high‐speed photography and sonography in the gel phantom show the same conclusion as that in the simulation. Ex vivo tissue experiments further confirmed that the presence of large axial shear strain in the gap zone. The ratios of axial shear strain in the porcine kidney and liver samples had statistical differences for two HIFU‐generated lesions without and with a gap (P < 0.05). Conclusions: Large axial shear strain induced by the acoustic radiation force from therapeutic HIFU burst only appears between two HIFU‐generated lesions with a gap between them. Transient ASSEs reconstructed immediately after the cession of HIFU exposure can easily, reliably, and sensitively detect the gap between produced lesions, which would provide real‐time feedback to enhance the success of HIFU ablation.